2014
DOI: 10.1103/physrevd.89.044002
|View full text |Cite
|
Sign up to set email alerts
|

Critical behavior of Born-Infeld AdS black holes in the extended phase space thermodynamics

Abstract: We study the thermodynamics of D-dimensional Born-Infeld AdS black holes in the extended phase space. We find that the usual small-large black hole phase transition, which exhibits analogy with the Van de Waals liquid-gas system, holds in all dimensions greater than three. However, different from the four-dimensional case, in the system of higher dimensional Born-Infeld AdS black holes there is no reentrant phase transition. For the three-dimensional Born-Infeld AS black hole, there does not exist critical phe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
143
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(145 citation statements)
references
References 63 publications
2
143
0
Order By: Relevance
“…Taking AdS black hole as a thermodynamic system, it was found that the phase transition of various AdS black holes are similar to that of the Van der Waals-Maxwell gas liquid [20,22,27]. Therefore, we can find some observable systems (Van der waals gas) similar to the AdS and dS background black holes.…”
Section: Discussionmentioning
confidence: 80%
“…Taking AdS black hole as a thermodynamic system, it was found that the phase transition of various AdS black holes are similar to that of the Van der Waals-Maxwell gas liquid [20,22,27]. Therefore, we can find some observable systems (Van der waals gas) similar to the AdS and dS background black holes.…”
Section: Discussionmentioning
confidence: 80%
“…Until now, these critical behaviour of a lot of black hole systems in this extended phase space are under discussion in this direction [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. It is worth to noting that, in four-dimensional Born-Infeld AdS black holes [4], the impact of the nonlinearity can bring the new phenomenon of reentrant phase transition which was observed in rotating AdS holes [19,20], while this reentrant phase transition does not occur for higher dimensional Born-Infeld AdS black holes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [57] shows that the RPTs only exist in the 4-dimensional Born-Infeld AdS black hole with a spherical horizon and also gives the proof that there is no reentrant phase transition in the system of higher (≥5) dimensional Born-Infeld AdS black hole. Reference [48] demonstrated that there only exists the Van der Waals-like phase transition in the 4-dimensional AdS black hole in massive gravity with Maxwell's electromagnetic field theory.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In recent two decades, exact solutions of gravitating black objects in the presence of BI theory have been vastly investigated. In the extended phase space, [56,57] recovered the RPT in the four-dimensional EinsteinBorn-Infeld AdS black hole with spherical horizon. However, for the higher-dimensional Einstein-Born-Infeld AdS black holes, there is no RPT.…”
Section: Introductionmentioning
confidence: 99%